One-step preparation of porous aminated-silica nanoparticles and their antibacterial drug delivery applications. (1st August 2020) - Wu, Yongren; Chen, Shun; Liu, Yang; Lu, Zhiwei; Song, Shaokun; Zhang, Yang; Xiong, Chuanxi; Dong, Lijie
Abstract: Porous functionalized silica nanoparticles have attracted the interest of researchers as they are excellent carriers for antibacterial drug delivery applications. In this work, porous aminated-silica nanoparticles (SiO2 -NH2 NPs) were prepared via one-step approach through the ammonia-catalyzed hydrolysis of tetraethylorthosilicate (TEOS) and (3-aminopropyl) triethoxysilane (APTES) in a mixed water–ethanol system. The obtained SiO2 -NH2 NPs displayed a spherical morphology and relatively uniform size distribution, while the morphology and structure of SiO2 -NH2 NPs were mainly determined by the order of the reagents added and the pH value of the solution. After characterization, the results showed that there were a large number of –NH2 groups on the surface of porous SiO2 -NH2 NPs and that the porous SiO2 -NH2 NPs had a large surface area of 476 m² g −1 with an average pore width of 4.3 nm. Through an absorbing–releasing experiment and bacterial test, those SiO2 -NH2 NPs were found to exhibit efficient absorption and release of drugs as well as a pH-dependent release pattern of epirubicin-loaded SiO2 -NH2 NPs. Meanwhile, SiO2 -NH2 @capsaicin NPs exhibited antibacterial properties. Those porous SiO2 -NH2 NPs could be a candidate for drug delivery for antibacterial applications owing to their tailored porous structure and high surface area.